Come on Over: Analyst/Investor Days as a Disclosure Medium - Kirk, Marcus P.; Markov, Stanimir (The Accounting Review, 2016)
ABSTRACT Our study introduces analyst/investor days, a new disclosure medium that allows for private interactions with influential market participants. We also highlight interdependencies in the choice and information content of analyst/investor days and conference presentations, a well-researched disclosure medium that similarly allows for private interactions. Analyst/investor days are less frequent, but with longer duration and greater price impact than conference presentations. They are mostly hosted by firms that already have opportunities to interact with investors at conferences, but whose complex and diverse activities make the short duration and rigid format of a conference presentation an imperfect solution to these firms' information problems. Analyst/investor days and conference presentations tend to occur in different quarters, consistent with their competing for the time and attention of senior management. When these two mediums are scheduled in close temporal proximity to each other, analyst/investor days diminish the information content of conference presentations, but not vice versa, consistent with managers' favoring analyst/investor days over conference presentations as a disclosure medium. JEL Classifications: D82; M41; G11; G12; G14. Data Availability: Data are publicly available from the sources identified in the paper.